A Study of Waste Transaction Practices and Islamic Jurisprudence at Bank Sampah - Ghani, Firhan Abdillah; Apriantoro, Muhamad Subhi (Ethica: International Journal of Humanities and Social Science Studies, 2023)
Garbage is a big problem for people who produce so much waste every day and are also quite disturbed by its unpleasant smell. This study aims to see how the transaction model of buying and selling waste saving system at the Berkah Lestari 3 Waste Bank. There are two problems studied in this study, namely: 1. How is the waste buying and selling transaction activity of the saving system at the Berkah Lestari 3 Waste Bank in Sewulan Village, Dagangan District, Madiun Regency. 2. What is the view of Islamic law on the transaction of buying and selling waste in the savings system at the Berkah Lestari 3 Garbage Bank in Sewulan Village, Dagangan District, Madiun Regency. The purpose of this study is to find out how the activities and perspectives of Islamic law views on buying and selling carried out at the Berkah Lestari 3 Garbage Bank. This research uses field research (field research) namely by direct field research to directly obtain information, observations, data, and interesting facts in the field then the data is described, analyzed to answer the formulation of the problem, from the results of the research found that, 1. This waste buying and selling transaction activity in practice the process of depositing waste can be directly deposited into the waste bank or can also be taken directly to the house by the waste bank if the customer cannot deliver it. In the process of taking garbage directly to the customer's home, it does not weigh and record the results on the spot but is carried out at the waste bank collection point, so that the customer does not know directly how many results they get. 2. The view of Islamic law on the sale and purchase transaction of the savings system at the Berkah Lestari 3 Garbage Bank is still allowed, because this waste or used goods still has benefits. Although in practice it is not witnessed by customers during the weighing process and recording results, so it can cause an element of gharar.